ANALISIS IMPLIKASI DEEP LEARNING PADA PERKEMBANGAN KOGNITIF, EMOSIONAL, DAN PSIKOLOGIS SISWA SEKOLAH DASAR DI SD NEGERI 4 CEPOGO - Marfu’ah Marfu’ah; Indah Lestari; Moch Widjanarko (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to describe the implementation of a deep learning approach and its impact on the cognitive, emotional, and psychological development of fifth-grade students at SD Negeri 4 Cepogo. The research employed a qualitative method through observation and interviews. The findings indicate that teachers have begun to implement deep learning through problem-based learning, simple projects, reflective discussions, and the use of digital media. This implementation has a positive impact on student development, including improvements in critical thinking skills, self-confidence, emotional regulation, independence, and curiosity. The challenges identified include limited time, instructional media, and teachers’ understanding of the approach. Teachers’ efforts to address these challenges include scaffolding, the use of simple media, group work, and training related to the Merdeka Curriculum. Overall, deep learning contributes significantly to improving the quality of both the learning process and student learning outcomes.